2012
DOI: 10.1186/1756-0500-5-19
|View full text |Cite
|
Sign up to set email alerts
|

In search of work/life balance: trainee perspectives on part-time obstetrics and gynaecology specialist training

Abstract: BackgroundPart-time training (PTT) is accessed by approximately 10% of Australian obstetrics and gynaecology trainees, a small but increasing minority which reflects the growing demand for improved work/life balance amongst the Australian medical workforce. This survey reports the attitudes and experiences of both full-time and part-time trainees to PTT.MethodsAn email-based anonymous survey was sent to all Australian obstetrics and gynaecology trainees in April 2009, collecting demographic and training status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…In a study, for the part-time model, the program completion rate was found to be low although the motivation of residents was high. 22 In the same study, part-time students stated that their education and research facilities were better or equal to full-time students but their continuity of care was lower. Continuity of care is one of the most important topics for family medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, for the part-time model, the program completion rate was found to be low although the motivation of residents was high. 22 In the same study, part-time students stated that their education and research facilities were better or equal to full-time students but their continuity of care was lower. Continuity of care is one of the most important topics for family medicine.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is stated that this trend is also rising worldwide including Europe, North America, Asia, Australia and Africa. [9][10][11][12][13][14][15][16][17][18][19] In Switzerland, 44 specialist degrees can be obtained with part-time courses. 10 Increased interest in parttime training is linked to feminization in medical education.…”
Section: Resultsmentioning
confidence: 99%
“…Implementing change at an institutional and organisational level is challenging but holds potential to have widespread positive impact on female perceptions and experience with CTS. More flexible training pathways, as seen in other specialties such as obstetrics and gynaecology, which also allow for less than full time training 35 , 36 could help overcome this barrier. Moreover, there should be greater support, understanding and acceptance from senior colleagues for trainees who consider taking time out of training.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate of 18.2 % must be considered relatively low compared to other online surveys [43]. However, online surveys among physicians reported similar low response rates such as Henry et al with a response rate of 20 % [44]. This could be explained by the fact that participants (1) were approached only once, (2) had expired or wrong e-mail addresses and (3) file or spam filters were activated.…”
Section: Limitationsmentioning
confidence: 91%